Class struggle and economic fluctuations: VAR analysis of the post-war U.S. economy - Deepankar Basu; Ying Chen; Jong-seok Oh (University of Massachusetts, Department of Economics, 2012)
Building on Marx's insights in Chapter 25, Volume I of Capital, an augmented version of the cyclical profit squeeze (CPS) theory offers a plausible explanation of macroeconomic fluctuations under capitalism. The pattern of dynamic interactions that emerges from a 3-variable (profit share, unemployment rate and nonresidential fixed investment) vector autoregression estimated with quarterly data for the postwar U.S. economy is consistent with the CPS theory for the regulated (1949Q1 - 1975Q1) as well as for the neoliberal periods (starting in 1980 or in 1985). Hence, the CPS mechanism seems to be in operation even under neoliberalism.
Keywords: B51; C22; 330; cyclical profit squeeze; vector autoregression